Morphology and Morphometry of Mandible of Stripped Hyena (Hyena hyena) - Pandya, Sweta; Bhayani, D.M.; Vyas, Y.L. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The morphological and morphometrical study of mandibles of hyena was carried out at Sakkarbaug Zoo, Junagadh (Gujarat). The average weight, length and width of mandible was 0.221 kg, 14.25 cm and 1.84 cm, respectively. The mandible was formed by two symmetrical halves fused rostrally by symphysis. The average length of symphysis mandibularis was 4.75 cm. The alveolar border presented six alveoli for lower incisors, two large deep alveoli for canine teeth, three alveoli for premolars and one for molar teeth. The diastemal mandibular length was 2.69 cm. The mental foramen was one. The mandibular height up to condylar and coronoid processes were 9.16 and 6.74 cm, respectively. The distance of mandibular foramen from posterior border was 3.22 cm. The angular process was placed at caudal border of horizontal ramus and found pointed and laterally curved. The average length of angular process was 1.23 cm.